The Position of Testimony in the Court Evidentiary System: A Juridical-Normative Analysis of Indonesian Law and Islamic Courts - Erniawati; Abdul Halim Talli; Zulhas’ari Mustafa; Mohamad Subli (PT. Nawa Edukasi Nusantara, 2026)
Testimony constitutes an essential evidentiary instrument within Indonesian and Islamic judicial systems, yet its application encounters practical complexities. This research aims to analyze the position of testimony in court evidentiary systems through a juridical-normative approach by comparing Indonesian positive law and Islamic law. The method employed is normative juridical with qualitative analysis of legal norms, testimony concepts, and case studies. Research findings indicate that: (1) Testimony regulation in KUHAP adheres to the negative legal system, while Islamic judiciary implements testimony hierarchy based on case types with more rigid standards; (2) Validity requirements for testimony in positive law emphasize procedural-formal aspects, whereas Islamic law applies the principles of 'adalah and dhabt with comprehensive tazkiyah al-syuhud mechanism; (3) The evidentiary position of testimony in Indonesian system is flexible with Constitutional Court Decision No. 65/PUU-VIII/2010 expanding acceptance of testimonium de auditu, while Islamic system applies the principle of